Considerations for the design, analysis and presentation of in vivo studies. Issue 3 (March 2017) - Ranstam, J.; Cook, J.A.
Summary: Objective: To describe, explain and give practical suggestions regarding important principles and key methodological challenges in the study design, statistical analysis, and reporting of results from in vivo studies. Conclusions: Pre-specifying endpoints and analysis, recognizing the common underlying assumption of statistically independent observations, performing sample size calculations, and addressing multiplicity issues are important parts of an in vivo study. A clear reporting of results and informative graphical presentations of data are other important parts.